(untitled) (University Journal of Zoology, Rajshahi University, 2008)
Toxicity, repellency and residual effects of Bishkatali plant extracts in chloroform and ethyl alcohol solvents were evaluated against the red flour beetle. Five concentrations viz. 500, 250, 125, 62.5 and 31.25mg/ml of Bishkatali plant extracts of both solvents were used in the experiment. The plant extracts in both solvents were moderately toxic to Tribolium castaneum. The toxicity of ethyl alcohol extract was more than chloroform extract after 24 and 72 hours treatment on the insect. Bishkatali plant extract in both solvents showed strong repellency against T. castaneum in which chloroform extract was better than ethyl alcohol extract. The rate of repellency was increased with the increment of concentration. Both the extracts have produced remarkable residual effect in reducing the progeny of T. castaneum. The lowest numbers of F1 adult progeny (32.7, 25.3 and 27.0) emerged from the wheat flour treated with 500mg/10g chloroform extract when parent released at 7, 12, 17 days after treatment respectively. Whereas with 500mg/10g ethyl alcohol extract, 38.0, 29.7 and 30.3 F1 adult progeny emerged when parents released at 7, 12, 17 days after treatment respectively. Bishkatali plant extracts in both chloroform and ethyl alcohol had remarkable residual effects on T. castaneum by reducing the production of F1 progeny and/or by increasing the population mortality. Key words: Botanical, solvent, red flour beetle, mortality, progeny, repellency, residual Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 93-97